Монголын тусгаар тогтнол ба эдийн засгийн хүчин зүйл (XIX зууны сүүлч, XX зууны эхэн үе) (Journal of International Studies, 2003)
English title: The economic factor of Mongolian independence (in the latter half of XIX and the beginning of XX centuries)